Role of IGSF10 mutations in self-limited delayed puberty. (25th February 2016) - Howard, Sasha; Guasti, Leo; Ruiz-Babot, Gerard; Mancini, Alessandra; David, Alessia; Storr, Helen; Metherell, Louise; Sternberg, Michael; Cabrera, Claudia; Warren, Helen; Barnes, Michael; Wehkalampi, Karoliina; et al.
Abstract: Background: Abnormal timing of puberty affects over 4% of adolescents and is associated with adverse health and psychosocial outcomes. Previous studies estimate that 60–80% of variation in the timing of pubertal onset is genetically determined. However, little is known about the genetic control of human puberty. Self-limited delayed puberty segregates in an autosomal dominant pattern; our study aimed to identify novel genetic regulators of disease in these patients. Methods: We performed whole-exome sequencing in 18 families with self-limited delayed puberty from our cohort, followed by candidate gene sequencing in a further 42 families. The functional consequences of the identified mutations in one candidate gene were interrogated via expression of wild type and mutant proteins in mammalian cells. For this gene we defined tissue expression in human and mouse embryos. The effects of gene knockdown were assessed via in-vitro neuronal migration assays, and in vivo with a transgenic zebrafish model. Findings: In ten unrelated families, we identified four rare mutations in IGSF10 in individuals with self-limited delayed puberty (adjusted p value after rare variant burden testing=3·4 × 10 –2 ). The identified mutations were in evolutionarily conserved positions, and two mutations resulted in intracellular retention with failure in secretion of the N-terminal fragment of the protein. IGSF10 mRNA was strongly expressed in the nasal mesenchyme in mouse and human embryos during migration of gonadotropin-releasing hormone (GnRH) neurons from their nasal origin towards the hypothalamus. IGSF10 knockdown caused reduced migration of immature GnRH neurons in the in-vitro analysis, and perturbed migration and extension of GnRH neurons in the zebrafish model. Interpretation: Our findings strongly support the contention that mutations in IGSF10 cause delayed puberty in human beings, through misregulation of GnRH neuronal migration during embryonic development. Funding: Wellcome Trust (102745), Rosetrees Trust (M222), and the Barts and the London Charity (417/1551) (SH); Biotechnology and Biological Sciences Research Council (BB/L002671/1) (LG and GB); LD is partly supported by the Academy of Finland (14135); National Institutes for Health Research (NIHR) (MB, HW, and CC); Medical Research Council (MR/K021613/1) (AD); Telethon Foundation (GP13142) (AC); VA is partly supported by a COST STSM (BM1105-16145) and a travel grant sponsored by Development (The Company of Biologists Ltd).